Correspondence relative to emigration of Chinese coolies - White, James T.; Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1853)
Colonial Office report containing information on the recruitment, transport and treatment of Chinese emigrants engaged to work as labourers in the British West Indies and Australia, including correspondence to and from James T. White, the British Government's agent in Hong Kong